2002
DOI: 10.1021/ma020630g
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical Properties of Chiral Substituted Polyfluorenes

Abstract: Liquid-crystalline polyfluorene (PF) homopolymers substituted with chiral alkyl side chains were synthesized, and their chiroptical properties in the solid state were investigated by means of circular dichroism (CD), circularly polarized photoluminescence (CPPL), and circularly polarized electroluminescence (CPEL) measurements. Polarization-selective scattering of light is shown to cause artifacts in the circularly polarized absorption and emission spectra in the wavelength range near or above the absorption e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
137
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 28 publications
11
137
0
Order By: Relevance
“…8 and 9. The change in shape of the CD must accordingly be attributed to the formation of an interchain aggregate in accordance with what was observed by Langeveld-Voss et al 31 and Oda et al 32 In this scenario we assume that the 2B u state has been split into the two states given by the linear combination with energy eigenvalues E ± = E 2B u ± V ab / 2. As for the symmetry of the system, we note that the PPV systems can in principle be described by C 2h symmetry, 36,53 although this assumes an ideal conformation of the polymer chain.…”
Section: Circular Dichroismsupporting
confidence: 78%
See 3 more Smart Citations
“…8 and 9. The change in shape of the CD must accordingly be attributed to the formation of an interchain aggregate in accordance with what was observed by Langeveld-Voss et al 31 and Oda et al 32 In this scenario we assume that the 2B u state has been split into the two states given by the linear combination with energy eigenvalues E ± = E 2B u ± V ab / 2. As for the symmetry of the system, we note that the PPV systems can in principle be described by C 2h symmetry, 36,53 although this assumes an ideal conformation of the polymer chain.…”
Section: Circular Dichroismsupporting
confidence: 78%
“…In both systems the high energy component has a stronger absorption and this could in principle be due to an exciton splitting, presumably then from an in- trachain aggregate. The impact on the CD spectra of a polythiophene due the medium was investigated by LangeveldVoss et al, 31 and the result of their study is that a CD spectrum with a strong bisignate Cotton effect only is obtained for what is considered to be a poor solvent ͑mixture͒ for this particular polymer, and Oda et al 32 made the same observations for a polyfluorene. Both these authors therefore concluded that the medium had forced the polymers into an aggregated state.…”
Section: Circular Dichroismmentioning
confidence: 89%
See 2 more Smart Citations
“…Mesomorphic behavior is seen in many other conjugated polymer families containing alkyl side chain substituents 22,23,24 although the exact details are both backbone and side chain specific. It also extends to oligomers and oligofluorenes bearing chiral side chain substituents 25,26,27 and these show very rich phase behavior. The mesomorphic behavior of the PF8 polymer correlates with the existence of two distinct backbone conformations 15,28 referred to as the "alpha" or "beta" phase 29 .…”
Section: Introductionmentioning
confidence: 93%